Comparison in Conscious Rabbits of the Baroreceptor-Heart Rate Reflex Effects of Chronic Treatment with Rilmenidine, Moxonidine, and Clonidine - Parkin, Monique L.; Lim, Kyungjoon; Burke, Sandra L.; Head, Geoffrey A. (Frontiers in Physiology, 2016)
We investigated the effects of chronic subcutaneous treatment with centrally-acting antihypertensive agents moxonidine, rilmenidine and clonidine on the baroreflex control of heart rate (HR) in conscious normotensive rabbits over 3 weeks. Infusions of phenylephrine and nitroprusside were performed at week 0 and at weeks 1 and 3 of treatment to determine mean arterial pressure (MAP)-HR baroreflex relationships. A second curve was performed after intravenous methscopolamine to determine the sympathetic baroreflex relationship. The vagal component of the reflex was determined by subtracting the sympathetic curve from the intact curve. Clonidine and moxonidine (both 1 mg/kg/day), and rilmenidine (5 mg/kg/day), reduced MAP by 13  3, 15  2 and 13  2 mmHg, respectively, but had no effect on HR over the 3-week treatment period. Whilst all three antihypertensive agents shifted baroreflex curves to the left, parallel to the degree of hypotension, moxonidine and rilmenidine decreased the vagal contribution to the baroreflex by decreasing the HR range of the reflex whilst moxonidine also increased sympathetic baroreflex range and sensitivity. By contrast clonidine had little chronic effect on the cardiac baroreflex. The present study shows that second generation agents moxonidine and rilmenidine but not first generation agent clonidine chronically shift the balance of baroreflex control of HR toward greater sympathetic and lesser vagal influences. These changes if translated to hypertensive subjects, may not be particularly helpful in view of the already reduced vagal contribution in hypertension.